Assessing uncertainties in the predicted very high energy flux of globular clusters in the Cherenkov Telescope Array era. Issue 4 (19th November 2020) - Ndiyavala-Davids, Hambeleleni; Venter, Christo; Kopp, Andreas; Backes, Michael
ABSTRACT: Terzan 5 is the only Galactic globular cluster that has plausibly been detected in the very high energy range. Stacking upper limits by High-Energy Stereoscopic System on the integral γ-ray flux of a population of other globular clusters are very constraining for leptonic cluster emission models. We demonstrate that uncertainty in model parameters leads to a large spread in the predicted flux, and there are indeed regions in parameter space for which the stringent stacking upper limits are satisfied. We conduct two more case studies: we study the uncertainties in differential TeV flux for M15, showing that our model can satisfy the stringent MAGIC upper limits for this cluster, for typical cluster parameters. We also calculate the differential flux at TeV energies for ω Cen, from which five pulsars have recently been detected at radio energies. It is thus important to increase measurement accuracy on key model parameters in order to improve predictions of cluster fluxes so as to better guide the observational strategy of the Cherenkov Telescope Array.